Expression of the Neuroblastoma-Associated ALK-F1174L Activating Mutation During Embryogenesis Impairs the Differentiation of Neural Crest Progenitors in Sympathetic Ganglia - Vivancos Stalin, Lucie; Gualandi, Marco; Schulte, Johannes Hubertus; Renella, Raffaele; Shakhova, Olga; Mühlethaler-Mottet, Annick (Frontiers in Oncology, 2019)
Neuroblastoma (NB) is an embryonal malignancy derived from the abnormal differentiation of the sympathetic nervous system. The Anaplastic Lymphoma Kinase (ALK) gene is frequently altered in NB, through copy number alterations and activating mutations, and represents a predisposition in NB-genesis when mutated. Our previously published data suggested that ALK activating mutations may impair the differentiation potential of neural crest (NC) progenitor cells. Here, we demonstrated that the expression of the endogenous ALK gene starts at E10.5 in the developing sympathetic ganglia (SG). To decipher the impact of deregulated ALK signaling during embryogenesis on the formation and differentiation of sympathetic neuroblasts, Sox10-Cre;LSL-ALK-F1174L embryos were produced to restrict the expression of the human ALK-F1174L transgene to migrating NC cells (NCCs). First ALK-F1174L mediated an embryonic lethality at mid-gestation and an enlargement of SG with a disorganized architecture in Sox10-Cre;LSL-ALK-F1174L embryos at E10.5 and E11.5. Second, early sympathetic differentiation was severely impaired in Sox10-Cre;LSL-ALK-F1174L embryos. Indeed, their SG displayed a marked increase in the proportion of NCCs and a decrease of sympathetic neuroblasts at both embryonic stages. Third, neuronal and noradrenergic differentiations were blocked in Sox10-Cre;LSL-ALK-F1174L SG, as a reduced proportion of Phox2b+ sympathoblasts expressed bIII-tubulin and almost none were Tyrosine Hydroxylase (TH) positive. Finally, at E10.5, ALK-F1174L mediated an important increase in the proliferation of Phox2b+ progenitors, affecting the transient cell cycle exit observed in normal SG at this embryonic stage. Altogether, we report for the first time that the expression of the human ALK-F1174L mutation in NCCs during embryonic development profoundly disturbs early sympathetic progenitor differentiation, in addition to increasing their proliferation, both mechanisms being potential crucial events in NB oncogenesis.